2020
DOI: 10.1158/1538-7445.am2020-3182
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3182: Kindlin-1 expression is associated with EGFR/RAS/MAPK activation and response to MEK inhibitors in triple-negative breast cancer

Abstract: Background: Triple-negative breast cancer (TNBC) accounts for ~15% of all invasive breast cancers. This heterogeneous group of tumors is the most aggressive and difficult-to-treat subtype of breast cancer. We previously demonstrated that Kindlin-1 is overexpressed in TNBC and patients with high Kindlin-1 have a worse prognosis. We determined that Kindlin-1 plays a major role in the epithelial to mesenchymal transition, tumor growth and breast cancer metastasis. TNBC have also been reported to express high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, Kindlin-1, an intracellular focal adhesion protein, has been shown to increase the invasive capacity of breast cancer cells and promote lung metastasis by upregulating TGFβ-induced epithelial-mesenchymal transition [34,35]. Studies have shown that Kindlin-1 is overexpressed in TNBC and plays an important role in TNBC tumor growth, metastasis and prognosis [36]. Tumor cells that exhibit invasion are more likely to detach from the primary tumor site and enter the bloodstream, thereby increasing the number of CTCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kindlin-1, an intracellular focal adhesion protein, has been shown to increase the invasive capacity of breast cancer cells and promote lung metastasis by upregulating TGFβ-induced epithelial-mesenchymal transition [34,35]. Studies have shown that Kindlin-1 is overexpressed in TNBC and plays an important role in TNBC tumor growth, metastasis and prognosis [36]. Tumor cells that exhibit invasion are more likely to detach from the primary tumor site and enter the bloodstream, thereby increasing the number of CTCs.…”
Section: Introductionmentioning
confidence: 99%